Integrasi Literasi Digital, Sistem Pembayaran Digital, dan Teknologi Penerangan Jalan untuk Pemberdayaan Masyarakat Desa Cibuntu - Rafika Sari; Milda Nabilah Al-hamaz; Lutfi Anapri; Raina Andriani Putri; Muhamad Daffa Ghulam Pratama; Eko Irwanda; Kelvin Elvangga; M. Syahrul; Mochammad Afif Kurniawan; Muhammad Fathir Rizki Rivano; Muhammad Zafira Firdaus; Prayuda Bowono; Rifqi Maulana (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The rapid development of digital technology presents both opportunities and challenges for rural communities in education, economic activities, and environmental safety. In RW 13 Cibuntu Village, Bekasi Regency, limited digital literacy among students, low adoption of digital payment systems by MSME actors, and insufficient street lighting affecting community safety were identified as key issues. This community service program aimed to integrate digital literacy, QRIS-based digital payment systems, and street lighting technology to support technology-driven community empowerment. The implementation employed educational, participatory, and collaborative approaches, including digital literacy and online safety education for junior high school students, training on digital media utilization and QRIS for MSMEs, and installation of public street lighting in poorly lit areas. Evaluation was conducted through observation, discussion, and comparison of conditions before and after the program. The results indicate improved students’ understanding of safe digital media usage, increased MSME awareness of cashless transactions, and enhanced community safety following the installation of street lighting. The integration of these technological aspects contributed to strengthening community digital capacity, improving environmental quality, and supporting local economic activities. Therefore, integrated digital technology implementation can serve as a sustainable and adaptive model for rural community empowerment.